2001
DOI: 10.1038/sj.onc.1204473
|View full text |Cite
|
Sign up to set email alerts
|

Modulation in vitro of H-ras oncogene expression by trans-splicing

Abstract: In man, activated N-, K-and H-ras oncogenes have been found in around 30% of the solid tumours tested. An exon known as IDX, which has been described previously and is located between exon 3 and exon 4A of the c-Hras pre-mRNA, allows an alternative splicing process that results in the synthesis of the mRNA of a putative protein named p19. It has been suggested that this alternative pathway is less tumorigenic than that which results in the activation of p21. We have used the mammalian trans-splicing mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…To the best of our knowledge, this is the first example of naturally occurring heterologous trans ‐splicing between viral and cellular host RNA transcripts. Our finding is not entirely unexpected given that the artificial overexpression of foreign RNA precursors by transfection has clearly been demonstrated to cause trans ‐splicing [12–17]. Indeed, recent studies by Caudevilla et al [26] have shown that plasmids encoding the HIV‐nef viral transcript when expressed in CV‐1 cells is capable of trans ‐splicing with host cell RNA precursors, lending support to the idea that trans ‐splicing occurs naturally during viral infection.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first example of naturally occurring heterologous trans ‐splicing between viral and cellular host RNA transcripts. Our finding is not entirely unexpected given that the artificial overexpression of foreign RNA precursors by transfection has clearly been demonstrated to cause trans ‐splicing [12–17]. Indeed, recent studies by Caudevilla et al [26] have shown that plasmids encoding the HIV‐nef viral transcript when expressed in CV‐1 cells is capable of trans ‐splicing with host cell RNA precursors, lending support to the idea that trans ‐splicing occurs naturally during viral infection.…”
Section: Resultssupporting
confidence: 79%
“…Indeed, studies by Puttaraju et al [12] found that overexpression of a precursor trans ‐splicing molecule (PTM) that contained an RNA targeting sequence, an unpaired 3′ splice site (3′ ss) and the corrected gene sequence, could be used therapeutically to modify specific mutant RNAs. This approach has since been used both in vitro and in vivo to successfully repair mutant CFTR, Collagen 17A1 and h‐ ras mRNAs [13–16]. We used this approach in an attempt to correct mutations in mutant RET proto‐oncogene RNA precursors, but those experiments had an unexpected result [17].…”
Section: Introductionmentioning
confidence: 99%
“…A sequence element located within intron D2 represses splicing of the upstream intron D1. Exon IDX is known to be poorly included in the mature transcript in in vitro splicing of a two-intron pre-mRNA (19) and substrate N in this work. Hence, we focused on the possible roles of intronic sequences in regulating this alternative splicing.…”
Section: Resultsmentioning
confidence: 99%
“…As the Adenosine2719Guanosine mutant lowered the strength (Cohen et al, 1989) of the IDX 5' splice site (5'SS), the study of this mutant could be of help in providing answers as to how the IDX 5' SS is regulated. Therefore, we used human nuclear extracts to splice pre-mRNAs containing only this critical E3-D intron-E4A region to gain an indication of the level of alternative splicing -see Figure 1a, lane 2, and Codony et al (2001). These experiments yielded more p21 than p19 products (see Figure 1a, lane 2); thus indicating that in vitro the p21 pathway is favoured in these minigenes.…”
mentioning
confidence: 99%
“…Figure 2c shows that splicing of the cap-distal intron B is clearly activated by the presence of increasing amounts of SR proteins (see PB in lanes 4 -7 and lanes 9 -12 in Figure 2c), while the capproximal intron A splicing is rescued to a lesser extent (see products A in lanes 4 -7 and lanes 9 -12 in Figure (Vogel et al, 1997). The splicing reactions assays, E3-D intron-E4A probe, RNA sequencing and RNA gels were described elsewhere (Codony et al, 2001). Similarly, Adenosine2719Guanosine mutant was obtained from ile12N(G) plasmid (Cohen et al, 1989).…”
mentioning
confidence: 99%